Nutritional Intake and Oxygen Saturation in Adolescent Girls in Central Java, Indonesia - Anandari, Dian; Masfiah, Siti; Rubai, Windri Lesmana; Maqfiroch, Arrum Firda Ayu; Wijayanti, Siwi Pramatama Mars; Kurniawan, Arif; Saryono, Saryono; Aji, Budi (Department of Public Health, Faculty of Health Sciences, Jenderal Soedirman University, 2024)
Background Adolescents are usually thought of having a healthy condition, so study about their physical health, especially that related to lung condition is very limited. Indicator used for assessing lung condition is oxygen saturation. The study aimed to analyze the association of nutritional impact to low oxygen saturation in adolescent girls in Central Java, Indonesia. Methods This study used a cross-sectional design with 378 adolescent girls as respondents. To find which nutrition intake related to oxygen saturation, data of each nutrition intake and SpO2 level were analyzed using linear regression. Data of body mass index, hemoglobin level and upper arm circumference were also included in the analysis since previous research showed their correlation with oxygen saturation. Results The prevalence of low SpO2 in adolescent is 8.5%. The nutrition intake which statistically significant related to oxygen saturation were fat (p = 0.007; CI = -0.021, -0.003) and vitamin D (p = 0.037; CI = 0.005, 0.172). Conclusions Adolescent should decrease fat consumption, increase vitamin D consumption, and need to increase arm circumference by consuming more protein and living healthy lifestyle to avoid infectious diseases.